2007
DOI: 10.1007/s10856-007-3177-4
|View full text |Cite
|
Sign up to set email alerts
|

The adherence of Candida albicans to acrylic resin reinforced with different fibers

Abstract: One important aethiological factor in the pathogenesis of chronic atrophic candidosis is the presence of Candida albicans on the fitting surface of the dentures. Fibers may come into contact with oral mucosa during the finishing procedures of acrylic resins. The exposed fibers may provide mechanical retention for yeast cells at the interface of the components. The effect of two different glass fibers and two different environments were evaluated in respect of Candida albicans adhesion to the acrylic surface. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…This is in agreement with previous studies. 14,17,25,26 However, the findings disagree with one report indicating preconditioning with saliva has no effect on C. albicans adherence to acrylic, 22 while another study reported increased adherence in the presence of saliva. 24 In the present study, to reduce individual variations and standardize saliva quality, whole unstimulated saliva was collected from only one healthy donor.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is in agreement with previous studies. 14,17,25,26 However, the findings disagree with one report indicating preconditioning with saliva has no effect on C. albicans adherence to acrylic, 22 while another study reported increased adherence in the presence of saliva. 24 In the present study, to reduce individual variations and standardize saliva quality, whole unstimulated saliva was collected from only one healthy donor.…”
Section: Discussionmentioning
confidence: 78%
“…24 Nonetheless, a reduction in the levels of yeast adherence to acrylic resins in the presence of saliva has been found by other several authors. 14,17,25,26 Effective reduction of plaque accumulation on surfaces is considered a primary preventive measure. Scrubbing dentures decreased the number of contaminating organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the beginning these forces are important in the initial adhesion and then they cause further bonding and denture plaque formation. Saliva, serum, oral floara and surface topography and chemistry differences may affect this complicated process 29,30…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al21 compared the XTT reduction assay and the crystal violet assay and their data indicated a significant correlation between the two methods. Since there are several studies indicating that the adhesions of C. albicans to acrylic surfaces may be affected by several factors such as the saliva, serum, oral flora and sucrose rich diet, in vitro nature of the investigation was the limitation of our study 29. Many studies have demonstrated that body fluids, proteins, enzymes, electrolytes and lipids in vivo destroy biomaterials, cause roughness and make it easy for microorganisms to attach to the surfaces 32…”
Section: Discussionmentioning
confidence: 99%
“…During microbial colonization, cells produce acidic substances as an outcome of their natural metabolisms that affect the pH of the surface they are interacting with. On the other hand, pH of the medium to which the materials are exposed plays also a significant role on microbial colonization 41) . This study was undertaken in order to investigate the C. albicans adherence levels to commercial denture soft liners when they were exposed to two different human body secretions, namely saliva and nasal secretions that were artificially created.…”
Section: Discussionmentioning
confidence: 99%